Engaging Learners in Intercultural Learning through Digital Literature Circles in Tertiary EFL Classroom - Imamyartha, David; Bilqis, Mutiara; Puspa, Areta; Hudori, Rizki Febri Andika; Wahjuningsih, Eka (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
With the advent of technology, cultural diversities have encouraged language teachers in tertiary education to push the current pedagogical boundaries to seek the best fits for cultural learning, despite the little emphasis on interculturality in day-to-day language learning. Entrenched to Byram’s intercultural learning, this case study explored Indonesian tertiary EFL learners’ perspectives of their intercultural learning through digital literature circles (henceforth DLC) within the context of tertiary education. Forty-five freshmen were involved in reflective culturally-laden DLC, during three months of an Extensive Reading course. Research data were garnered from focus group discussion (FGD) and students’ reading logs in their DLC role sheets. Drawing on qualitative content analysis, this study has acknowledged that DLC evokes consciousness-raising, comparative interpretation, and criticality associated with intercultural communicative competence (ICC). Students voice the critical cultural awareness stemming from such transactional reading, manifest in richer propositions and ideas, deeper understanding of foreign and home cultures, and critical evaluation and reflection on cultures. The study corroborates the technological and socio-constructivist affordances of DLC to empower intercultural learning.